Agent-Based Modelling: A Methodology for Neo-Schumpeterian Economics - Andreas Pyka; Giorgio Fagiolo (Universität Augsburg, Institut für Volkswirtschaftslehre, 2005)
Modellers have had to wrestle with an unavoidable trade-off between the demand of a general theoretical approach and the descriptive accuracy required to model a particular phenomenon. A new class of simulation models has shown to be well adapted to this challenge, basically by shifting outwards this trade- off: So-called agent-based models (ABMs henceforth) are increasingly used for the modelling of socio-economic developments. Our paper deals with the new requirements for modelling entailed by the necessity to focus on qualitative developments, pattern formation, etc. which is generally highlighted within Neo-Schumpeterian Economics and the possibilities given by ABMs.
urn:nbn:de:bvb:384-opus4-711789
Keywords: O30; B52; 330; Simulation; Neo-Schumpeterian Economics; Agents